Research on the synergistic modification effect and the interface mechanism of GO/SBS compound-modified asphalt based on experiments and molecular simulations - Qing Zeng; Yaru Liu; Qicheng Liu; Zhenghong Xu (Scientific Reports, 2023)
Abstract Although there have been reports showing the modification effect of carbon nanomaterials on asphalt, there are few studies on whether carbon nanomaterials and polymers can have synergistic modification effects on asphalt. At the same time, the complex composition of asphalt makes it difficult to determine the interface mechanism between the modifier and the asphalt. In this study, graphene oxide (GO) and styrene–butadiene–styrene block copolymer (SBS) were selected as modifiers. A combined experimental and molecular simulation research method was used to study the synergistic modification effect and the interface mechanism between the modifier and the asphalt. The results show that the modification effect of GO/SBS incorporated into asphalt is significantly superior to that of GO or SBS incorporated individually and GO/SBS has a synergistic modification effect. Although the binding strength between SBS and asphalt is weak, the GO surface (GO (0 0 1)) can simultaneously bind with SBS and asphalt, increasing the binding strength of SBS and asphalt as well as promoting the dispersion of SBS in asphalt, so that GO/SBS shows a synergistic modification effect and improves properties such as low-temperature ductility, rheology and storage stability at macroscopic level. Intercalated and exfoliated structure can be formed between GO side (GO (0 1 0)) and asphalt, which improves the anti-aging properties of the asphalt. Physical bonding is the main interface binding for GO/SBS compound-modified asphalt. GO bonds to asphalt or SBS by hydrogen bonds and there are only dispersion forces between SBS and asphalt, resulting in a higher binding strength between GO and asphalt or SBS than between SBS and asphalt.